Introduction to computer graphics with OpenGL ES - Han, JungHyun (CRC Press, Taylor & Francis Group, 2018)
This book achieves a balance between theory and practice by presenting the fundamentals of game graphics and showing how they are implemented into Unity. This book also presents C# script code on many topics, providing a hands-on look at Unity graphics. Industry professionals as well as students in upper-level courses in Computer Graphics and Game Programming will find this book of immense value.